Lability of copper bound to humic acid - Mao, Lingchen; Young, Scott D.; Bailey, Liz (Elsevier, 2015)
Geochemical speciation models generally include the assumption that all metal bound to humic acid and fulvic acid (HA, FA) is labile. However, in the current study, we determined the presence of a soluble ‘non-labile’ Cu fraction bound to HA extracted from grassland and peat soils. This was quantified by determining isotopically-exchangeable Cu (E-value) and EDTA-extraction of HA-bound Cu, separated by size-exclusion chromatography (SEC) and assayed by coupled ICP-MS. Evidence of time-dependent Cu fixation by HA was found during the course of an incubation study (160 days); up to 50% of dissolved HA-bound Cu was not isotopically exchangeable. This result was supported by extraction with EDTA where approximately 40% of Cu remained bound to HA despite dissolution in 0.05 M Na2-EDTA. The presence of a substantial non-labile metal fraction held by HA challenges the assumption of wholly reversible equilibrium which is central to current geochemical models of metal binding to humic substances.